1982
DOI: 10.1139/v82-218
|View full text |Cite
|
Sign up to set email alerts
|

Some physical and chemical aspects of spin trapping of organometallic radicals by quinones: optically active radical complexes

Abstract: . Can. J. Chem. 60, 1504Chem. 60, (1982.A brief account is presented on the use of substituted quinones as spin traps for organometallic radicals and on the applications of CIDEP and esr-HPLC techniques to the study of quinone -organometallic radical complexes. Many of these radical adducts are thermally very stable and can be isolated by the HPLC technique for detailed spectroscopic and chemical studies. This in turn allows us to present a different approach to the "spin trapping" chemistry of unstable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…From the examination of the ir carbonyl bands, it can be concluded that the C,,, structure is the correct one for all of the monosubstituted radical complexes which were studied. This is in agreement with the rather large (-25 G) phosphorus coupling constants which were observed (21,22).…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…From the examination of the ir carbonyl bands, it can be concluded that the C,,, structure is the correct one for all of the monosubstituted radical complexes which were studied. This is in agreement with the rather large (-25 G) phosphorus coupling constants which were observed (21,22).…”
Section: Methodssupporting
confidence: 89%
“…However, a similar experiment with manganese carbonyls produced the radical complexes which decomposed while being eluted through a HPLC column. Since the rhenium carbonyl -quinone radicaI complexes undergo slow substitution reactions with a number of organolnetal donors (20)(21)(22), it follows that one could design kinetic experiments using the pure radical complexes. Furthermore, we have demonstrated (20,21) that the ligand substitution reactions involving optically active organometals and/or optically active quinones led to the isolation of some interesting optically active radical complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several nitro compounds have also been employed to trap alkyl-silyl radicals [51]. Recent reports indicate that nitro compounds can also complex manganese [52,53] and rhenium [53] centered radicals via both nitrogen and oxTgen atoms simultaneously, as shown below.…”
Section: Osne3 Ic"2rmentioning
confidence: 98%
“…thiobenzophenones (19). Thus, tin-, silicon-, and germaniumcentered radicals are systematically added to chromones, chromanone, and thiachromanones and the resulting radical adducts are reported in Table 2.…”
Section: -Chromanone Radicalmentioning
confidence: 99%